Pelatihan Guru SDNKetapang Dan SDNTanjung Anom Untuk Meningkatkan Keterampilan Memilih Metode Pembelajaran - Year Rezeki Patricia Tantu (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
This workshop was held based on the need for the teachers at SDN Ketapang and SDN Tanjung Anom, Tangerang to improve their skills in determining learning methods. In 2016-2017, those teachers attended a seminar on Classroom Action Research (CAR). As a follow up to the seminar, they needed a workshop on how to apply it in classroom teaching and learning. Thus, this workshop aims to give opportunities for those elementary teachers to understand the importance of CAR, reflect after teaching, identify classroom problems, identify the supporting theories, and choose the appropriate learning method to overcome the problems. The implementation of the activity begins with a needs analysis of the teacher, determining the topic and schedule of training, preparation of teaching material, training followed by questions and answer session, practice, and evaluation. The activity was held in March-May 2018 and was attended by 11 elementary teachers. The three-month workshop result was the improvement of skill in determining teaching and learning methods to overcome class problems through CAR framework. It was shown by the practice of class problem identification and learning method identified by the teachers.